Seasonal variation in canine anti-Leishmania infantum antibody titres. (May 2021) - Cavalera, M.A.; Iatta, R.; Panarese, R.; Mendoza-Roldan, J.A.; Gernone, F.; Otranto, D.; Paltrinieri, S.; Zatelli, A.
Highlights: Inter-seasonal variations in anti- Leishmania antibody titres in dogs were evaluated. In most dogs, antibody titres decreased in the non-transmission season. Interpretation of antibody titres must include the impact of the sand fly season. Annual screening for leishmaniosis should be performed in the non-transmission season. Abstract: Quantitative anti- Leishmania antibody titres are critical in the management of dogs with leishmaniosis, from diagnosis to treatment and follow-up, and there is a paucity of data relating changes in antibody titres to sand fly vector seasonality. This study aimed to evaluate seasonal variations in anti- Leishmania infantum antibody titres in dogs from a hyperendemic area for canine leishmaniosis (CanL). Leishmania infantum -seropositive and clinically healthy dogs ( n = 65) were sampled in June 2019 (sand fly season) and again in February-March 2020 (non-transmission season) to monitor clinical status and serological titres. There was a reduction in anti- L. infantum antibody titres during the non-transmission season in most dogs ( n = 36; 55.4%), and 44% of those dogs ( n = 16/36) became seronegative (i.e. below the cut-off value of 1:80). Given the relevance of serology to epidemiological, preventive and clinical studies related to CanL, seasonal variations in antibody titres are important in areas where phlebotomine vectors have seasonal patterns of activity. Sand fly seasonal period must be considered in the interpretation of annual anti- L. infantum antibody screening test results in asymptomatic dogs, to make clinical decisions about staging, treatment and prevention.